Daily nutrition in the Dalmatian Hinterland in the 1950s - Bosanac, Vesna, inženjerka prehrambene tehnologije (Array, 2021)
Against the backdrop of describing the traditional diet in different parts of Croatia, this paper presents the diet of the inhabitants of the Dalmatian Hinterland in the 1950s. The frequency of consumption of specific food groups and eating habits of the population at the time will be analysed. The paper emphasises the nutritional value of unprocessed foods and their health benefits and points to the importance of their share in modern human diet as often as possible.